The Rate of Infusion Represents an Important Aspect of Administering Anticancer Agents - Lan MJ; Yao DF; Zhu LL; Zhou Q (Dove Medical Press, 2023)
Mei-Juan Lan,1 Di-Fei Yao,2,3 Ling-Ling Zhu,4 Quan Zhou2 1Division of Nursing, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China; 2Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China; 3Key Laboratory of Intelligent Pharmacy and Individualized Therapy of Huzhou, Changxing Campus of the Second Affiliated Hospital of Zhejiang University, Huzhou, Zhejiang Province, People's Republic of China; 4VIP Geriatric Ward, Division of Nursing, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaCorrespondence: Quan Zhou, Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Jiefang Road No. 88, Shangcheng District, Hangzhou, Zhejiang Province, 310009, People's Republic of China, Email zhouquan142602@zju.edu.cn Ling-Ling Zhu, VIP Geriatric Ward, Division of Nursing, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of China, Email 2192022@zju.edu.cnBackground: Infusion rate is one of the essential elements that should be included in all intravenous orders. Patients may experience adverse consequences or risks associated with inappropriate infusion. Meanwhile, there is growing pressure on the chemotherapy unit to deliver treatment quickly, efficiently, and safely, and thus it is very necessary to improve the chemotherapy process and service to cancer patients. Clinicians should consider how to further standardize infusion therapy, and innovate new infusion strategies to increase efficacy, reduce toxicity, improve patient satisfaction and save health resource costs. Sporadic studies have evaluated the effects of infusion rates of anticancer agents on clinical outcomes, economic benefits, and administration efficiency. However, an update review has not been available.Methods: Relevant literature was identified by search of PubMed until September 2023.Results: Infusion rates may have significant effect on the efficacy of anticancer agents (e.g., methotrexate, fluorouracil, and arsenic trioxide). Slow infusion is safer for platinum compounds, doxorubicin and carmustine, whereas fast infusion is safer than slow infusion of gemcitabine. Optimal flow rates of paclitaxel and fluorouracil are based on the balance between multiple risks of toxicity. Optimal infusion rate may bring economic benefits. If efficacy and safety are not compromised, shortened infusion may result in higher patient satisfaction, improved institutional efficiency and more nursing time available for other activities (e.g., biosimilar products, endostar). Other concerns about infusion rate include clinical indications (eg, paclitaxel and rituximab, methotrexate), severity and type of hypersensitivity reactions (e.g., platinum compounds), formulation features (e.g., paclitaxel, doxorubicin), and genetic polymorphism (e.g., gemcitabine, methotrexate).Conclusion: The latest knowledge of infusion rate concerns will enhance the appropriateness and accuracy in intravenous administration. Interdisciplinary teams should collaborate and implement relevant risk management and healthcare policy. It is worthwhile to conduct comparative studies of intravenous therapy with different infusion speeds.Keywords: anticancer agents, efficacy, healthcare policy, infusion rate, medication administration, pharmacoeconomics, safety